The effect of spironolactone on calcineurin inhibitor induced nephrotoxicity: a multicenter randomized, double-blind, clinical trial (the SPIREN trial) - Line Aas Mortensen; Helle C. Thiesson; Birgitte Tougaard; Martin Egfjord; Anne Sophie Lind Fischer; Claus Bistrup (BMC Nephrology, 2018)
Abstract Background Calcineurin inhibitor induced nephrotoxicity contributes to late allograft failure in kidney transplant patients. Evidence points towards aldosterone to play a role in the development of fibrosis in multiple organs. Animal studies have indicated a beneficial effect of mineralocorticoid receptor antagonists preventing calcineurin inhibitor induced nephrotoxicity. Only few studies have explored this effect in humans. The objective of this study is to evaluate the effect of spironolactone on glomerular filtration rate and fibrosis in kidney transplant patients. Method Prospective, double-blind, randomized, clinical trial including 170 prevalent kidney transplant patients. Patients are randomized to spironolactone 25–50 mg/day or placebo for three years. Primary outcome is glomerular filtration rate evaluated by chrome-EDTA clearance. Secondary outcomes are 24-h protein excretion, amount of interstitial fibrosis in renal allograft biopsies, and cardiovascular events. As an exploratory outcome, we aim to identify markers of fibrosis in blood and urine. Discussion Long term allograft survival remains a key issue in renal transplantation, partly due to calcineurin inhibitor induced nephrotoxicity. Evidence from animal- and small human studies indicate a beneficial effect of mineralocorticoid receptor antagonism on renal function and fibrosis. This study aims to test this hypothesis in a sufficiently powered randomized clinical trial. Results might influence the future management of long term allograft survival in renal transplantation. Trial registration ClinicalTrials.gov identifier (05/17/2012): NCT01602861. EudraCT number (05/31/2011): 2011–002243-98.